2007
DOI: 10.1109/iembs.2007.4352665
|View full text |Cite
|
Sign up to set email alerts
|

Older Adult Perceptions of Smart Home Technologies: Implications for Research, Policy & Market Innovations in Healthcare

Abstract: Advances in information communications technology and related computational power are providing a wide array of systems and related services that form the basis of smart home technologies to support the health, safety and independence of older adults. While these technologies offer significant benefits to older people and their families, they are also transforming older adults into lead adopters of a new 24/7 lifestyle of being monitored, managed, and, at times, motivated, to maintain their health and wellness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
139
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(147 citation statements)
references
References 15 publications
5
139
2
1
Order By: Relevance
“…Coughlin et al, for example, found that service providers and policy advocates were particularly passionate about ethical considerations in smart home technologies, especially trust and privacy issues, 24/7 home monitoring and third party use of behavioural data by commercial entities (Coughlin et al, 2007). However, van Hoof et al in their research into the prototype of a home-based autonomous surveillance system for older users, found that users themselves were not worried about privacy issues, and did not feel watched or monitored (2011).…”
Section: Surveying Ethical Issues In Intelligent Environmentsmentioning
confidence: 99%
“…Coughlin et al, for example, found that service providers and policy advocates were particularly passionate about ethical considerations in smart home technologies, especially trust and privacy issues, 24/7 home monitoring and third party use of behavioural data by commercial entities (Coughlin et al, 2007). However, van Hoof et al in their research into the prototype of a home-based autonomous surveillance system for older users, found that users themselves were not worried about privacy issues, and did not feel watched or monitored (2011).…”
Section: Surveying Ethical Issues In Intelligent Environmentsmentioning
confidence: 99%
“…Personal privacy can also be understood as a freedom, to "escape being observed or accessed when desired" (Essén 2008, p. 130), implying a social duty to respect the desire for isolation of others. The introduction of H-IoT may cause a gradual loss of personal privacy (Steele et al 2009), particularly among smart home systems (Coughlin et al 2007;Demiris 2009;Dorsten et al 2009). Monitoring technologies can create a psychological disturbance, sometimes called obtrusiveness (Hensel et al 2006;Nefti et al 2010), expressed in a feeling of 'being watched'.…”
Section: Personal Privacymentioning
confidence: 99%
“…On the social side, personal privacy concerns control over social interaction through geographical distance, group membership, and location. It is connected to physical privacy (Bagüés et al 2007b;Coughlin et al 2007;Little and Briggs 2009) and can contribute to social isolation. For H-IoT used in chronic illness management, potential violations of personal privacy can be justified on the basis of 'need' for the technology, derived from safety concerns (Zwijsen et al 2011;Steele et al 2009) or the delay of a move to residential care (Townsend et al 2011;Remmers 2010;Essén 2008;McLean 2011).…”
Section: Personal Privacymentioning
confidence: 99%
See 2 more Smart Citations